An investigation on the effectivenss of nailed timber walls as retrofitting measure for substandard concrete structures - Keser, Aslı. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Turkey is in a seismically active region and has suffered through extensive losses due to several major earthquakes that struck its various parts. The destructive effects of earthquakes in Turkey are infuriated by the large volume of buildings constructed with low quality materials and workmanship. Especially a great percentage of residential buildings are constructed by using substandard concrete and reinforcement. Furthermore, research shows a great possibility of a high magnitude earthquake to occur in the near future around the Marmara region, which includes the most populated cities in Turkey. Inevitably, there is a need for an effective and affordable retrofitting method. In this study, a new retrofitting method is introduced and its effect on the seismic performance of two representative case study buildings are investigated. The retrofitting method consists of the implementation of timber walls which are prepared with nails. Initially, cyclic shear tests are performed on two types of nailed timber walls in an effort to obtain stiffness and strength properties. The only difference between the nailed timber walls is the number of nails used. Computational simulations of the experimental tests are generated in CSI Perform3D with buckling restrained brace elements. Two simulations of each case study reinforced concrete buildings retrofitted with the two types of nailed timber walls are conducted along with the original reinforced concrete building. Finally, the seismic performances of structural models are compared with each other. For the first case study building, which is a well-designed building with substandard material quality, it is concluded that even though the seismic performance of the representative building is slightly increased, a comprehensive enhancement in seismic performance is not achieved with the retrofitting method investigated. For the second case study building, which is a poorly designed building with low material quality, seismic performance is significantly improved.
Keywords: Earthquakes -- Turkey.; Wooden-frame houses.